Applying Discussion Method to Improve Qur'anic Studies Learning Outcomes for Junior High School Students - Asep Ramdan; Nursobah, Asep (Jurnal Keprofesian Guru Keagamaan, 2024)
This study aims to describe the application of the discussion method in improving learning outcomes in the subject of Al-Qur'an Hadith (Qurdis) in grade VIII Odd Semester MTs Darul Mumtazin, Ciparay District, Bandung Regency, Academic Year 2021/2022. The formulation of this research problem is how the application of the discussion method can improve student learning outcomes. This research uses an action research method consisting of two cycles, where each cycle includes the stages of design, implementation and observation, reflection, and revision. The subject of the study was grade VIII students in the Odd Semester. Data collection is carried out through written tests and practice tests. The results of the study show that the discussion method is effective in improving student learning outcomes. In Cycle I, 76.9% of students (10 out of 13 students) achieved completeness, while in Cycle II it increased to 92% of students (12 out of 13 students). With an increase of 15.1% from Cycle I to Cycle II, it was concluded that the discussion method succeeded in improving learning outcomes and achieving completeness in Cycle II.